Model Kajian Kebijakan Peningkatan Penemuan Penderita Malaria di Daerah Remote Area (Sulit dan Terpencil) (Journal of Telenursing (JOTING), 2025)
This study aims to find a policy study model for increasing the discovery of malaria sufferers in remote areas (challenging geography and topography) of malaria endemic areas to accelerate malaria elimination in TTS Regency, NTT Province. The method used is a case study survey method with a retrospective study design, population, and sample determination using purposive techniques, namely several health centers in moderate endemic areas. The results of the study showed that 1). The number of laboratory personnel with analyst qualifications or medical laboratory personnel is still very lacking. 2). Difficult laboratory facilities are still very lacking, such as reagents are limited and reagent storage places do not meet requirements. 3). Budget/cost support for the malaria elimination program is still very lacking. 4). Geographical and topographic conditions and accessibility are difficult in remote areas. In conclusion, government policies related to malaria elimination have been determined, but implementing policies in the program is still limited. To achieve malaria elimination, it is necessary to decide on a model/form of malaria case-finding policy in areas with complex topography in moderate malaria-endemic areas. Keywords: Health Policy, Malaria, Sufferer Discovery